Utilization of Preventive Dental Services Before and After Health Insurance Covered Dental Scaling in Korea: 2009 to 2014 Community Health Survey. (January 2017) - Jang, Young-Eun; Kim, Chun-Bae; Kim, Nam-Hee
Health insurance reduces the economic burden of diseases and enhances access to medical services. This study compared, among social classes, the utilization of preventive dental service before and after health insurance covered dental scaling. We analyzed time-series secondary data for 3 175 584 participants from 253 survey areas nationwide in the Community Health Survey (2009-2014) in Korea. The weighted proportion of participants who underwent dental scaling was defined as the scaling rate. Data regarding demographic and socioeconomic characteristics were collected. Scaling rates continuously increased over the 6-year period, particularly in 2014. College graduates had significantly higher scaling rates. Monthly income and scaling rate were positively related. Differences by education decreased over time. Differences by income were particularly high between 2012 and 2014. For women, the temporal rate was 2 times higher for professionals than for the unemployed. Despite increased dental scaling rates since the health coverage change in 2013, socioeconomic differences persist.